2016
DOI: 10.1002/ejp.927
|View full text |Cite
|
Sign up to set email alerts
|

Putting pain out of mind with an ‘out of body’ illusion

Abstract: Background: Chronic pain is a growing societal concern that warrants scientific investigation, especially given the ineffectiveness of many treatments. Given evidence that pain experience relies on multisensory integration, there is interest in using body ownership illusions for reducing acute pain. Aim: In the present study, we investigate whether patients' experience of chronic pain could be reduced by full body illusions (FBIs) that cause participants to dissociate from their own body. Methods: Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Also it has been found that if there is body ownership over a virtual body and then participants are lifted out of that body, there is a strong physiological response (Heart Rate Deceleration) to an attack seen on that body, with the HRD correlating with the questionnaire scores on body ownership [18]. In a recent study Pamment and Aspell [40] compared the two paradigms that we have adapted here to examine their influence on chronic pain. They found that patients’ ratings of pain substantially reduced during a virtual out-of-body experience, but that there was no overall difference in ratings between the two OBE paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Also it has been found that if there is body ownership over a virtual body and then participants are lifted out of that body, there is a strong physiological response (Heart Rate Deceleration) to an attack seen on that body, with the HRD correlating with the questionnaire scores on body ownership [18]. In a recent study Pamment and Aspell [40] compared the two paradigms that we have adapted here to examine their influence on chronic pain. They found that patients’ ratings of pain substantially reduced during a virtual out-of-body experience, but that there was no overall difference in ratings between the two OBE paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be shown to what extent some of the divergent results can be explained by methodological differences (Mohan et al., ; Nierula et al., ). For full body illusions (FBI), it has be shown that a higher strength of illusion is related to higher pain thresholds (Hänsel et al., ), reduced arousal response to painful stimuli (Romano et al., ) and reduced habitual pain in chronic pain patients (Pamment and Aspell, ), suggesting that the degree of ownership for the seen body plays an important role for pain‐modulating effects during FBI.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, pain and body perception are essentially two subjective mutually influencing perceptual experiences Trojan et al, 2014): the fast and accurate perception of pain is essential to protect the body, and the perception of body integrity is needed to avoid pain . Thus, the study of errors in processing the explicit (conscious) and implicit (unconscious) body experience, as in the case of illusion phenomena (Medina and Coslett, 2016b), may represent a useful opportunity to understand how the brain constructs functional representations of the body in patients with MDRDs, and on pain perception itself (Pamment and Aspell, 2017;Fang et al, 2019) in these clinical conditions. However, existing studies on SoP, SpP, and BO were largely conducted on healthy subjects (Longo et al, 2008a;Fuentes et al, 2013;Longo, 2017), and clinical research has mostly investigated neurological conditions (Haggard and Wolpert, 2005;Pia et al, 2013Pia et al, , 2016, eating disorders (Keizer et al, 2011;Scarpina et al, 2014;Spitoni et al, 2015;Gadsby, 2017), and neuropathic pain syndromes such as Complex Regional Pain Syndrome-CRPS (Galer and Jensen, 1999;Förderreuther et al, 2004;Lewis et al, 2007;Reinersmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%